Calcium/calmodulin-dependent protein kinase (CaMK) Iα mediates the macrophage inflammatory response to sepsis - Zhang, Xianghong (Society for Leukocyte Biology, 2011)
Dysregulated Ca(2+) handling is prevalent during sepsis and postulated to perpetuate the aberrant inflammation underlying subsequent organ dysfunction and death. The signal transduction cascades mediating these processes are unknown. Here, we identify that CaMKIα mediates the Mφ response to LPS in vitro and the inflammation and organ dysfunction of sepsis in vivo. We show that LPS induced active pThr(177)-CaMKIα in RAW 264.7 cells and murine peritoneal Mφ, which if inhibited biochemically with STO609 (CaMKK inhibitor) or by RNAi, reduces LPS-induced production of IL-10. Transfection of constitutively active CaMKIα (CaMKI293), but not a kinase-deficient mutant (CaMKI293(K49A)), induces IL-10 release. This production of IL-10 is mediated by CaMKIα-dependent regulation of p38 MAPK activation. CaMKIα activity also mediates the cellular release of HMGB1 by colocalizing with and regulating the packaging of HMGB1 into secretory lysosomes. During endotoxemia, mice receiving in vivo CaMKIα(RNAi) display reduced systemic concentrations of IL-10 and HMGB1 in comparison with mice receiving NT(RNAi). These data support the biological relevance of CaMKIα-dependent IL-10 production and HMGB1 secretion. In a CLP model of sepsis, CaMKIα(RNAi) mice display reduced systemic concentrations of IL-10, IL-6, TNF-α, and HMGB1 in comparison with NT(RNAi) mice, which correlate with reductions in the development of renal dysfunction. These data support that CaMKIα signaling is integral to the Mφ responding to LPS and may also be operant in vivo in regulating the inflammation and organ dysfunction consequent to sepsis.